Accuracy of GPS devices for measuring high-intensity running in field-based team sports - Rampinini, E.; Alberti, G.; Fiorenza, M.; Riggio, M.; Sassi, R.; Borges, T. O.; Coutts, A. J. (International Journal of Sports Medicine, 2015)
We compared the accuracy of 2 GPS systems with different sampling rates for the determination of distances covered at high-speed and metabolic power derived from a combination of running speed and acceleration. 8 participants performed 56 bouts of shuttle intermittent running wearing 2 portable GPS devices (SPI-Pro, GPS-5 Hz and MinimaxX, GPS-10 Hz). The GPS systems were compared with a radar system as a criterion measure. The variables investigated were: total distance (TD), high-speed distance (HSR>4.17 m·s-1), very high-speed distance (VHSR>5.56 m·s-1), mean power (Pmean), high metabolic power (HMP>20 W·kg-1) and very high metabolic power (VHMP>25 W·kg-1). GPS-5 Hz had low error for TD (2.8%) and Pmean (4.5%), while the errors for the other variables ranged from moderate to high (7.5-23.2%). GPS-10 Hz demonstrated a low error for TD (1.9%), HSR (4.7%), Pmean (2.4%) and HMP (4.5%), whereas the errors for VHSR (10.5%) and VHMP (6.2%) were moderate. In general, GPS accuracy increased with a higher sampling rate, but decreased with increasing speed of movement. Both systems could be used for calculating TD and Pmean, but they cannot be used interchangeably. Only GPS-10 Hz demonstrated a sufficient level of accuracy for quantifying distance covered at higher speeds or time spent at very high power.